Does Employment Generation Really Matter For Poverty Reduction ? - Gutiérrez Sourdis, Catalina 1994- (The World Bank, 2007)
This paper analyzes how the employment/productivity profile of growth and its sectoral pattern are correlated with poverty reduction. The authors use a sample of 104 short-run growth spells in developing countries, between 1980 and 2001. They also identify some conditions of the labor market and the economic environment that are associated with employment-intensive growth or specific sectoral growth. The results show that, in the short run, although the aggregate employment-rate intensity of growth does not matter for poverty reduction any more than the aggregate productivity intensity of growth, the sectoral pattern of employment growth and productivity growth is important. Employment-intensive growth in the secondary sector is associated with decreases in poverty, while employment-intensive growth in agriculture is correlated with poverty increases. Similarly, productivity-intensive growth in agriculture is associated with decreases in poverty. Although the study does not address causality, coincidence of these phenomena in this large sample of heterogeneous countries and periods suggests that, in the short run, the sectoral productivity and employment pattern of growth may have important implications for poverty alleviation. Therefore, policies for reducing poverty should not overlook the sectoral productivity and employment implications of different growth policies